Characteristic Time Scales of Decadal to Centennial Changes in Global Surface Temperatures Over the Past 150 Years. Issue 4 (20th April 2020) - Le Mouël, J. L.; Lopes, F.; Courtillot, V.
Abstract: We apply singular spectral analysis (SSA) to series of monthly mean values of surface air temperatures T, International sunspot number (ISSN), and polar faculae PF (1850–2017 for T and ISSN). The efficiency of the SSA algorithm that we use has been regularly improved. For the T, ISSN, and PF series, the SSA eigenvalues and first components are shown with their Fourier spectrum. Components of T, ISSN, or PF share similar periods. Most are found in solar activity. The 22‐ and 11‐year components are modulated and drift in phase, reflecting slight differences in spectra. On the shorter‐period side, components at 9, 5.5, and 4.7 years are in good agreement. They have been identified in solar activity. The 60‐year component is prominent in T . It is not immediately apparent in ISSN but can be extracted with an appropriate choice of SSA window. Other types of data allow one to explore longer periods and confirm climatic variations at 60, 35, and 22 years and at 50–150 and 200–500 years. When we consider a longer ISSN series starting in 1700 and recalculate the SSA first component, the trends of solar activity and temperature over the time span from 1850 to 2017 are very similar, with slower rise before 1900 and after the late 1900s, separating a faster rise in much of the twentieth century. These trends, extracted over only 150 years, could be parts of longer, multicentennial changes in solar activity. Much of the variability of surface temperatures could be linked to the Sun. Key Points: We analyze the four main data sets of global surface temperatures (1850‐2017) with the powerful method of singular spectral analysis We find spectral periods typical of variations in solar activity It can be argued that much of the variability of surface temperatures could be natural and primarily controlled by the Sun